Cyberbullying : development, consequences, risk and protective factors : a special issue of the European journal of developmental psychology - Menesini, Ersilia; Spiel, Christiane; European Society for Developmental Psychology (Abingdon, Oxon, UK : Psychology Press, 2012)
'From the beginning of 2000, with the increase and diffusion of modern technologies, a new form of bullying using electronic means has emerged. Literature has reached some consistent findings on the description of the problem. However, there is still a lack of knowledge about developmental processes of cyberbullying and about possible predictors and correlates. Some of the main emerging areas investigated in connection with cyberbullying are: personality factors, callous unemotional traits and self-control, memory cognitive distortions, emotional and moral mechanisms, ICT use and media exposure, family and social contexts. Another important issue is the relation between cyberbullying and face to face bullying. From face to face literature we know some of the mechanisms in the peer group such as the relation between bullying, dominance and popularity and the role of bystanders in the social dynamic of the attacks. However, nothing is known about the cyber community. Contributions of this volume attempt to investigate these group mechanisms in the cyber community. Finally, for the victims, long-term consequences are also relevant, both in terms of perceived stress level and the association between cyber-victimization and mental health. This special issue offers important new findings on the development and consequences of cyberbullying and cyber-victimization, and opens new and future directions of research.'--P. [4] of cover.
Introduction : Cyberbullying: development, consequences, risk and protective factors / Ersilia Menesini and Christiane Spiel -- A longitudinal study of cyberbullying : examining risk and protective factors / Kostas A. Fanti, Andreas G. Demetriou and Veronica V. Hawa -- Recalling unpresented hostile words : false memories predictors of traditional and cyberbullying / Manila Vannucci, Annalaura Nocentini, Giuliana Mazzoni, and Ersilia Menesini -- Cyberbullying and traditional bullying in adolescence : differential roles of moral disengagement, moral emotions, and moral values / Sonja Perren and Eveline Gutzwiller-Helfenfinger -- Cyberbullying in context : direct and indirect effects by low self-control across 25 European countries / Alexander T. Vazsonyi, Hana Machackova, Anna Sevcikova, David Smahel and Alena Cerna -- Cyber-victimization and popularity in early adolescence : stability and predictive associations / Petra Gradinger, Dagmar Strohmeier, Eva Maria Schiller, Elisabeth Stefanek and Christiane Spiel -- Processes of cyberbullying, and feelings of remorse by bullies : a pilot study / Robert Slonje, Peter K. Smith and Ann Fris{u296E} --How stressful is online victimization? Effects of victim's personality and properties of the incident / Frithjof Staude-M$1#7H(Bler, Britta Hansen and Melanie Voss -- The association between the mental health and behavioural problems of students and their reactions to cyber-victimization / Julian J. Dooley, Therese Shaw, and Donna Cross.s
'This book is a reproduction of the European Journal of Developmental Psychology, volume 9, issue 2.'--T.p. verso.
Includes bibliographical references and index.
Keywords: Cyberbullying; Bullying; Internet and teenagers; Internet and children